AltaGas Club Professional Coach Program (2009)
The AltaGas Club professional coach support program is designed to increase the number of Canadian clubs delivering year round, full service programs. Through the sponsorship and support of AltaGas, CCC will identify clubs whereby financial support can assist in creating sustainable full time professional club coaching positions. The current sponsorship agreement with AltaGas will be reviewed in June 2010 with the intent on renewing terms beyond June 2011. Our plan is to offer a three (3) year program to clubs pending successful renegotiations with the sponsor and an annual review of the progress made by each club. The contribution over the three year term will include grants ranging from 15 000$ the first year to 12 000$ the second year to 8 000$ the third and final year. Clubs that are looking to hire a full time coach for the first time in 2009-10 will receive higher consideration but clubs that have only hired a full time coach for the first time in 2008-09 are also eligible for this funding program and will be considered as in the 2nd year of the agreement (12 000$ grant for 09-10).